Wilhelm Stenhammar as an actor in the late 19th century musical life of Stockholm: Suggestions for new perspectives and interpretations through digital musicology - Reese Willen, Anne (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2023)
This article presents a reevaluation of Wilhelm Stenhammar’s role in Stockholm’s late 19th-century musical scene, challenging traditional views of the 1880s as a time of decline. The article aims to provide new insights into Stenhammar’s early career, his involvement in musical networks, and his contributions as a chamber musician. Utilizing digital musicology, this article revisits the work of Bo Wallner, who has had a significantly impact on the understanding of Swedish music at the turn of the twentieth century. By analyzing digitized newspapers and periodicals, the study presents new insights into the concert scene and musical repertoire from the mid-19th century to the first decades of the 20th century. This article underscores the possibilities of digital tools in historical musicology, especially for visualizing and analyzing concert performances and musical networks. It reveals a more vibrant and dynamic musical environment in Stockholm than previously recognized, highlighting Stenhammar’s substantial contributions as a chamber musician and his involvement in the city’s musical networks. The article also demonstrates the potential of digital methodologies in reconstructing historical narratives. The study enriches the understanding of Stockholm’s musical life in the late 19th century, portraying it as a fertile period for musicians like Stenhammar. Keywords: Wilhelm Stenhammar, Stockholm’s musical life, late 19th century, early 20th century, Bo Wallner, digital musicology, networks.